2017
DOI: 10.1002/jcb.25901
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles Analysis and Functional Characterization of MicroRNA-660 in Skeletal Muscle Differentiation

Abstract: MicroRNA are a series of small non-coding RNAs that have emerged as critical regulators of skeletal muscle development. Here, we concentrated on the function of miR-660 during bovine skeletal myogenesis from our previous high-throughput sequencing results, then analyzed its expression profiles and characterized related functional roles. Overexpression of miR-660 significantly attenuated myogenic differentiation of C2C12 cells, whereas miR-660 inhibition enhanced C2C12 differentiation. Dual-Luciferase Reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The development of bovine skeletal muscle is a complex process involving prenatal and postnatal patterns, which are mainly due to all muscle fiber formation, the muscle fiber size increases and new muscle fibers regenerate, respectively (Buckingham et al, 2003). In our research, two developmental stages were chosen: the embryonic 90-day stage, a prenatal generation when a large amount of muscle progenitor cell proliferation occurs; and the adult 24-month-old stage, during which myofibers are well established (Hocquette, 2010; Yue et al, 2017). Considering the differential expression of RNAs from these two stages, these RNAs might be associated with myogenesis, particularly lncRNAs and miRNAs that are known to have more developmental stage-specific expression patterns than protein-coding genes (Guttman and Rinn, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The development of bovine skeletal muscle is a complex process involving prenatal and postnatal patterns, which are mainly due to all muscle fiber formation, the muscle fiber size increases and new muscle fibers regenerate, respectively (Buckingham et al, 2003). In our research, two developmental stages were chosen: the embryonic 90-day stage, a prenatal generation when a large amount of muscle progenitor cell proliferation occurs; and the adult 24-month-old stage, during which myofibers are well established (Hocquette, 2010; Yue et al, 2017). Considering the differential expression of RNAs from these two stages, these RNAs might be associated with myogenesis, particularly lncRNAs and miRNAs that are known to have more developmental stage-specific expression patterns than protein-coding genes (Guttman and Rinn, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle-specific miRNAs, including miR-1 9 , miR-133 10 , miR-206 11 , miR-208 12 , and miR-499 13 , have been considered key regulators with different targets during muscle development. Moreover, ubiquitously expressed miRNAs, such as miR-128 14 , miR-27 15 , miR-155 16 , miR-378 17 , miR-486 18 , miR-29 7 , miR-29b 19 , miR-34b 20 , miR-152 21 , and miR-660 22 , have been found to be crucial factors affecting the formation of skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The mature miRNA with the RISC, in most cases, binds to the 3'-untranslated region (3'-UTR) of the target mRNAs to elicit translation inhibition and/or degradation of the target transcripts (Figure 1 ) 18 . Research has shown that miRNAs play critical roles in a myriad of biological processes, including proliferation 19 , differentiation 20 , 21 , and apoptosis 22 of cells, immune response 23 , and angiogenesis 24 .…”
Section: Biogenesis and Functions Of Mirnas And Lncrnasmentioning
confidence: 99%